Ca(2+)/calmodulin-dependent protein kinase II regulates cardiac Na(+) channels - Wagner, Stefan (American Society for Clinical Investigation, 2006)

(untitled)
In heart failure (HF), Ca(2+)/calmodulin kinase II (CaMKII) expression is increased. Altered Na(+) channel gating is linked to and may promote ventricular tachyarrhythmias (VTs) in HF. Calmodulin regulates Na(+) channel gating, in part perhaps via CaMKII. We investigated effects of adenovirus-mediated (acute) and Tg (chronic) overexpression of cytosolic CaMKIIδ(C) on Na(+) current (I(Na)) in rabbit and mouse ventricular myocytes, respectively (in whole-cell patch clamp). Both acute and chronic CaMKIIδ(C) overexpression shifted voltage dependence of Na(+) channel availability by –6 mV (P < 0.05), and the shift was Ca(2+) dependent. CaMKII also enhanced intermediate inactivation and slowed recovery from inactivation (prevented by CaMKII inhibitors autocamtide 2–related inhibitory peptide [AIP] or KN93). CaMKIIδ(C) markedly increased persistent (late) inward I(Na) and intracellular Na(+) concentration (as measured by the Na(+) indicator sodium-binding benzofuran isophthalate [SBFI]), which was prevented by CaMKII inhibition in the case of acute CaMKIIδ(C) overexpression. CaMKII coimmunoprecipitates with and phosphorylates Na(+) channels. In vivo, transgenic CaMKIIδ(C) overexpression prolonged QRS duration and repolarization (QT intervals), decreased effective refractory periods, and increased the propensity to develop VT. We conclude that CaMKII associates with and phosphorylates cardiac Na(+) channels. This alters I(Na) gating to reduce availability at high heart rate, while enhancing late I(Na) (which could prolong action potential duration). In mice, enhanced CaMKIIδ(C) activity predisposed to VT. Thus, CaMKII-dependent regulation of Na(+) channel function may contribute to arrhythmogenesis in HF.